Microwave‐Assisted Tragacanth Gum–Based Grafted Silver Nanocomposite Hydrogel for Sustained Release Formulations of Diclofenac Sodium and Antibacterial Assay - Sharanappa Chapi; Gangadhar Babaladimath; M. V. Murugendrappa; Anjanapura V. Raghu (Nano Select, 2024)
ABSTRACT In this work, novel tragacanth gum‐graft‐poly(2‐acrylamido‐2‐methylpropanesulfonic acid) (TG‐g‐PAMPS) hydrogel was synthesized via free radical copolymerization of TG, 2‐acrylamido‐2‐methylpropanesulfonic acid by using ammonium peroxodisulfate and N,N‐methylene‐bis‐acrylamide under microwave radiation, resulting in the cross‐linked graft copolymer network. Silver nanoparticles (SNs) were formed and stabilized by the reduction of silver nitrate using tri‐sodium citrate. The TG‐g‐PAMPS gel and its nanocomposite were characterized and confirmed using FTIR, TGA, XRD, SEM, EDS, and TEM techniques. It is observed that the presence of SNs significantly improves the swelling ability of the TG‐g‐PAMPS gel. Degradation studies of both hydrogels were studied using the soil burial method and determining the respective weight loss. The presence of SNs is found to impart significant antibacterial properties to the gel against Pseudomonas aeruginosa and Escherichia coli bacteria. Further, the TG‐g‐PAMPS gel and TG‐g‐PAMPS‐SN were evaluated as matrix materials for the release of the drug (diclofenac sodium) and the effect of SNs on the release was examined. The in‐vitro released data were analyzed using empirical equations to understand the mechanism of release. Among the various models, the released data were well fitted into the Korsmeyer–Peppas equation and the released kinetics followed non‐Fickian diffusion.